2012
DOI: 10.1080/13617672.2012.732810
|View full text |Cite
|
Sign up to set email alerts
|

Religious diversity, empathy, and God images: perspectives from the psychology of religion shaping a study among adolescents in the UK

Abstract: Major religious traditions agree in advocating and promoting love of neighbour as well as love of God. Love of neighbour is reflected in altruistic behaviour and empathy stands as a key motivational factor underpinning altruism. This study employs the empathy scale from the Junior Eysenck Impulsiveness Questionnaire to assess the association between empathy and God images among a sample of 5,993 religiously diverse adolescents (between the ages of 13-and 15-years) attending state-maintained schools in England,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 56 publications
(83 reference statements)
1
27
0
1
Order By: Relevance
“…Religiosity has been associated, for example, with increased empathy, although not across the board. For example, religious participants who believed in a merciful God were higher in empathy and those who believe in a God of justice were lower (Francis, Croft & Pyke, 2012). Duriez (2004) has also shown that empathy and most of its sub-dimensions are associated with symbolic (versus literal) styles of religiosity, but was not associated with simply identifying as religious.…”
Section: Limitations and Concluding Commentsmentioning
confidence: 99%
“…Religiosity has been associated, for example, with increased empathy, although not across the board. For example, religious participants who believed in a merciful God were higher in empathy and those who believe in a God of justice were lower (Francis, Croft & Pyke, 2012). Duriez (2004) has also shown that empathy and most of its sub-dimensions are associated with symbolic (versus literal) styles of religiosity, but was not associated with simply identifying as religious.…”
Section: Limitations and Concluding Commentsmentioning
confidence: 99%
“…In most of the schools visited in collecting OFSTED evidence, pupils clearly understood the importance of learning about the diversity of religion and belief in contemporary society (OFSTED, 2010). This finding is supported by qualitative and quantitative research in English schools conducted as part of a European project (Ipgrave& McKenna, 2008;McKenna, Neill & Jackson,2009) and by a project on Young People's Attitudes Towards Religious Diversity in the United Kingdom conducted by the University of Warwick as part of the Religion and Society programme (eg Francis et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…Unfortunately, the loving God scale they used consisted of semantic differential items (e.g., forgiving–unforgiving), in which the opposite end of the adjectives that described a loving God were often adjectives that describe a punitive God, and thus confounded beliefs in a loving with beliefs in a punitive God. Although we found other studies that explored how adolescents view God, they either combined measures of a loving and punitive God to form a single instrument (e.g., Francis, Croft, & Pyke, ), or provided insufficient information to draw conclusions (e.g., Meier & Meier, ).…”
Section: Belief In a Punitive God Versus Loving Godmentioning
confidence: 95%